Increased Adaptive Variation Despite Reduced Overall Genetic Diversity in a Rapidly Adapting Invader - Selechnik, Daniel; Richardson, Mark F.; Shine, Richard; DeVore, Jayna L.; Ducatez, Simon; Rollins, Lee A. (Frontiers in Genetics, 2019)
Invasive species often evolve rapidly following introduction despite genetic bottlenecks that may result from small numbers of founders; however, some invasions may not fit this “genetic paradox.” The invasive cane toad (Rhinella marina) displays high phenotypic variation across its introduced Australian range. Here, we used three genome-wide datasets to characterize their population structure and genetic diversity. We found that toads form three genetic clusters: (1) native range toads, (2) toads from the source population in Hawai’i and long-established areas near introduction sites in Australia, and (3) toads from more recently established northern Australian sites. Although we find an overall reduction in genetic diversity following introduction, we do not see this reduction in loci putatively under selection, suggesting that genetic diversity may have been maintained at ecologically relevant traits, or that mutation rates were high enough to maintain adaptive potential. Nonetheless, toads encounter novel environmental challenges in Australia, and the transition between genetic clusters occurs at a point along the invasion transect where temperature rises and rainfall decreases. We identify environmentally-associated loci known to be involved in resistance to heat and dehydration. This study highlights that natural selection occurs rapidly and plays a vital role in shaping the structure of invasive populations.